2019
DOI: 10.1016/j.ijhydene.2019.10.080
|View full text |Cite
|
Sign up to set email alerts
|

Modeling hydrogen networks for future energy systems: A comparison of linear and nonlinear approaches

Abstract: Common energy system models that integrate hydrogen transport in pipelines typically simplify fluid flow models and reduce the network size in order to achieve solutions quickly. This contribution analyzes two different types of pipeline network topologies (namely, star and tree networks) and two different fluid flow models (linear and nonlinear) for a given hydrogen capacity scenario of electrical reconversion in Germany to analyze the impact of these simplifications. For each network topology, robust demand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Nonlinear programming plays a crucial role in addressing a wide range of practical engineering problems. It is mainly used in energy supply systems [59,60] (such as natural gas [61][62][63], petroleum, electricity, etc.) and pipeline water distribution systems [64][65][66] (such as urban and rural water distribution networks and water supply networks).…”
Section: Nonlinear Programming Methodsmentioning
confidence: 99%
“…Nonlinear programming plays a crucial role in addressing a wide range of practical engineering problems. It is mainly used in energy supply systems [59,60] (such as natural gas [61][62][63], petroleum, electricity, etc.) and pipeline water distribution systems [64][65][66] (such as urban and rural water distribution networks and water supply networks).…”
Section: Nonlinear Programming Methodsmentioning
confidence: 99%
“…optimizing the hydrogen transmission or distribution networks such as [13] who developed an approach for designing a hydrogen pipeline network, and [14] who used designed a hydrogen pipeline network in Germany using GIS. Furthermore, [15] compared the modelling of hydrogen pipelines with linear and non-linear approaches, finding that linear approaches are largely appropriate, but that their solutions should be checked for feasibility. Other papers have focused on optimizing the entire supply chain, including production, storage and transport.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nevertheless, it has been shown that the more detailed project-based modelling of transport infrastructure entails a negligible cost difference compared to the induced computational burden. 71 A potential future research would be the assessment of limited installation rates for the green hydrogen production facilities. The results, however, might lead to higher investments in blue hydrogen supply facilities that might become stranded assets in the long run.…”
Section: Limits and Further Researchmentioning
confidence: 99%